2013
DOI: 10.1007/s11420-013-9361-9
|View full text |Cite
|
Sign up to set email alerts
|

MR Appearance and Clinical Significance of Changes in the Hip Muscles and Iliopsoas Tendon after Arthroscopic Iliopsoas Tenotomy in Symptomatic Patients

Abstract: Background: Iliopsoas tenotomy is a treatment for snapping hip. Does this surgical procedure change the surrounding muscle and tendon anatomy? Questions/ Purposes: This study seeks to evaluate the changes in the MR appearance of the hip muscles and iliopsoas tendon in patients following arthroscopic iliopsoas tenotomy. Methods: One hundred sixty-nine consecutive adults were evaluated after iliopsoas tenotomy at the lesser trochanter. Each MR exam was evaluated independently by three radiologists for muscle ede… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
33
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
5
5

Relationship

1
9

Authors

Journals

citations
Cited by 34 publications
(40 citation statements)
references
References 11 publications
5
33
2
Order By: Relevance
“…Iliopsoas atrophy was seen by MRI evaluation of 20 patients who had underwent a psoas tenotomy at the level of the lesser trochanter 45 . Iliacus and psoas muscle atrophy were present in 65% and 85% of the patients in the study.…”
Section: Treatmentmentioning
confidence: 99%
“…Iliopsoas atrophy was seen by MRI evaluation of 20 patients who had underwent a psoas tenotomy at the level of the lesser trochanter 45 . Iliacus and psoas muscle atrophy were present in 65% and 85% of the patients in the study.…”
Section: Treatmentmentioning
confidence: 99%
“…The results of Blomberg et al 6 may also explain in part the finding that although 25% of the lesser trochanteric patients in the study by Hain et al 15 developed gluteus maximus atrophy, none of the labral-level tenotomy patients in the current study did. This may have occurred because the smaller muscle mass left intact after lesser trochanteric tenotomies resulted in a greater loss of the normal opposition to hip extension generated by the iliacus and psoas muscles, and thus, the development of gluteus maximus atrophy.…”
Section: Discussionmentioning
confidence: 43%
“…Another interesting finding was that the atrophy was not associated with a significant decrease in hip function. In fact, there was no significant difference in the modified HHS of the patients with no atrophy, mild to moderate atrophy, and severe iliacus or psoas muscle atrophy at two years follow-up, and the majority of the patient's with grade 4 atrophy showed good clinical outcomes 27 . According to this this study, other Authors reported a significant clinical @ C I C E d i z i o n i I n t e r n a z i o n a l i loss of flexion strength after surgery in all patients but they improved in a period lasting from 6 to 10 weeks 26,29 .…”
Section: @ C I C E D I Z I O N I I N T E R N a Z I O N A L Imentioning
confidence: 82%